2014
DOI: 10.1653/024.097.0347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astilbin fromDimorphandra mollis(Fabaceae) Flowers and Brazilian Plant Extracts onSitophilus zeamais(Coleoptera: Curculionidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The present study supports the earlier work of Kangade and Zambare (2013) where 100% mortality of rice moth was observed in methanol extract of Argemone mexicana. Similar results were also obtained by Tavares et al (2014) that ethanol extract of T. diversifolia flower caused higher mortality and repellency of Sitophillus zeamais and Sitotroga cerealella (Fouad et al, 2014). The methanol extract of T. diversifolia leaves were toxic to C. maculatus (Green et al, 2017) and Anopheles gambiae (Ileke et al, 2019).…”
Section: Resultssupporting
confidence: 84%
“…The present study supports the earlier work of Kangade and Zambare (2013) where 100% mortality of rice moth was observed in methanol extract of Argemone mexicana. Similar results were also obtained by Tavares et al (2014) that ethanol extract of T. diversifolia flower caused higher mortality and repellency of Sitophillus zeamais and Sitotroga cerealella (Fouad et al, 2014). The methanol extract of T. diversifolia leaves were toxic to C. maculatus (Green et al, 2017) and Anopheles gambiae (Ileke et al, 2019).…”
Section: Resultssupporting
confidence: 84%
“…The leaf extract from Senna obtusifolia (L.) H.S. Irwin & Barneby (Fabaceae) showed repellency activity of class II (between 20.1-40%) to control adults of Sitophilus zeamais (Motschulsky) (Coleoptera: Dryophthoridae) (de Souza Tavares et al 2014). For its part, the ethyl acetate extract of the seeds (EtOAc) and secondary metabolites of Senna tora (L.) Roxb.…”
Section: Discussionmentioning
confidence: 99%
“…Previous phytochemical studies have allowed the identification of a variety of compounds found in Senna spp., including alkaloids (Moo-Puc et al 2007), anthraquinones (Branco et al 2011), cardiac glycosides (Essiett & Bassey 2013), glucosides (sennosides) (Monkheang et al 2011), naphthopyrones (Graham et al 2004), phenols (Viegas Junior et al 2013, saponins (Oluwole et al 2016), triterpenes, (Luximon-Ramma et al 2002, among others. The metabolic content of Senna species has been associated with a variety of biological properties, including insecticidal activity (Yagi et al 2013;de Souza Tavares et al 2014;Vasudev et al 2015). Senna crotalarioides (Cassia crotalarioides Kunth [Fabaceae]) is an arborous species distributed in various states of Mexico (Estrada et al 2004).…”
Section: Palabras Clave: Botánico; Gusano Cogollero De Maíz; Insecticmentioning
confidence: 99%